A case study in the implementation of data envelopment analysis - Ng, Kin Wei, 1985-; Rohanin Ahmad, supervisor; Fakulti Sains (2009)
Thesis (Sarjana Sains (Matematik)) - Universiti Teknologi Malaysia, 2009